Efecto de las propiedades físicas del suelo en el contenido de agua en zonas aluviales de uso agrícola, rio Buenavista. - Guzman Armijos, Jose Alejandro; Sanchez Peña, Holger Fernando (Machala : Universidad Técnica de Machala, 2023)
This research examines the effect of the physical properties of the soil on the water content in alluvial areas for agricultural use on the "Pedro Ramos" farm located in the La Victoria parish, Santa Rosa canton, El Oro province, Ecuador. The objective is to evaluate how apparent density, real density, electrical conductivity (EC), pH and soil texture affect water retention and, consequently, the productivity of the banana crop. To achieve the objectives of the study, a comprehensive methodology was used that included location, research design, and data collection both in the field and in the laboratory and equipment such as GPS, Imacimus 10 multiparametric meter and potentiometer. The investigation began with a topographical survey of the property using GPS, and the data was processed with AutoCAD (2019) to create a plan in accordance with MAG regulations. The study adopted a descriptive observational approach, without a control group, to describe and measure the variables over a short period. The variables evaluated in the banana crop included the height of the offspring, number of leaves, weight of hands and rachis, number of fingers, volumetric humidity, and nitrates. The results revealed that the apparent density and the true density showed asymmetric distributions, with means less than the medians, reflecting a variability in the physical properties of the soil that affects the retention of water and nutrients. The low standard deviation in bulk density and moderate variability in true density indicate relative homogeneity and differences in soil composition, respectively. Electrical conductivity presented low variability, suggesting a uniform distribution of salts, while pH showed low variability, indicating well-managed soils. The texture of the soil presented a high variability, which impacts its ability to retain water and nutrients. Daily rainfall showed an irregular distribution, with peaks in June and February, which is crucial for agricultural planning. Volumetric soil moisture showed variability over 10 weeks, with high outliers in some weeks, suggesting inconsistent irrigation issues. The negative correlation between apparent density and porosity suggests that denser soils have lower porosity, while effective porosity has an important relationship with pH. The study concludes that the physical properties of the soil significantly influence water retention and agricultural productivity. Constant monitoring of these properties, implementation of soil moisture sensors, and adjustment of irrigation practices to ensure uniform water distribution are recommended. Soil texture should also be improved by adding organic matter and agricultural activities should be adjusted based on rainfall data. Furthermore, it is suggested to develop strategies to optimize water retention and continue investigating the correlations between soil properties and their impact on water and nutrient retention.
Esta investigación examina el efecto de las propiedades físicas del suelo en el contenido de agua en zonas aluviales de uso agrícola en la finca "Pedro Ramos" situada en la parroquia La Victoria, cantón Santa Rosa, provincia de El Oro, Ecuador. El objetivo es evaluar cómo la densidad aparente, densidad real, conductividad eléctrica (CE), pH y textura del suelo afectan la retención de agua y, en consecuencia, la productividad del cultivo de banano. Para alcanzar los objetivos del estudio, se utilizó una metodología integral que incluyó la localización, el diseño de investigación, y la recolección de datos tanto en campo como en laboratorio y equipos como GPS, medidor multiparamétrico Imacimus 10 y potenciómetro. La investigación comenzó con el levantamiento topográfico de la finca utilizando GPS, y los datos fueron procesados con AutoCAD (2019) para crear un plano conforme a las normativas del MAG. El estudio adoptó un enfoque observacional descriptivo, sin grupo control, para describir y medir las variables durante un breve período. Las variables evaluadas en el cultivo de banano incluyeron la altura del hijo, número de hojas, peso de manos y raquis, número de dedos, humedad volumétrica, y nitratos. Los resultados revelaron que la densidad aparente y la densidad real mostraron distribuciones asimétricas, con medias menores que las medianas, reflejando una variabilidad en las propiedades físicas del suelo que afecta la retención de agua y nutrientes. La baja desviación estándar en la densidad aparente y la variabilidad moderada en la densidad real indican una homogeneidad relativa y diferencias en la composición del suelo, respectivamente. La conductividad eléctrica presentó baja variabilidad, sugiriendo una distribución uniforme de sales, mientras que el pH mostró baja variabilidad, indicando suelos bien manejados. La textura del suelo presentó una alta variabilidad, lo que impacta su capacidad para retener agua y nutrientes. La pluviometría diaria mostró una distribución irregular, con picos en junio y febrero, lo cual es crucial para la planificación agrícola. La humedad volumétrica del suelo mostró variabilidad a lo largo de 10 semanas, con valores atípicos altos en algunas semanas, lo que sugiere problemas de riego inconsistente. La correlación negativa entre densidad aparente y porosidad sugiere que suelos más densos tienen menor porosidad, mientras que la porosidad efectiva tiene una relación importante con el pH. El estudio concluye que las propiedades físicas del suelo influyen significativamente en la retención de agua y la productividad agrícola. Se recomienda un monitoreo constante de estas propiedades, la implementación de sensores de humedad del suelo, y el ajuste de las prácticas de riego para asegurar una distribución uniforme del agua. También se debe mejorar la textura del suelo mediante la adición de materia orgánica y ajustar las actividades agrícolas basadas en datos de pluviometría. Además, se sugiere desarrollar estrategias para optimizar la retención de agua y continuar investigando las correlaciones entre las propiedades del suelo y su impacto en la retención de agua y nutrientes.
Keywords: RETENCION DE AGUA; PROPIEDADES FISICAS DEL SUELO; PLUVIOMETRIA